Determinant Model of Graduate Competence Partnership-based Life Skills Training in the Industry 4.0 Era - Tri Suminar; Yudi Siswanto; Sri Wardani; Amin Yusuf; Islahuddin Islahuddin (Universitas Negeri Semarang, 2024)
The competence of life skills training graduates in the industrial era 4.0 must be in line with the needs of work competencies and adapt 21st century skills, but the results of the evaluation of training programs at the Institute of Courses and Training (LKP) show that the absorption of training graduates is still low, ranging from 35%-44%. The research objectives are (a) to identify the validity and reliability of indicators of factors that play a role in the competence of graduates of life skills training; (b) to obtain a causal relationship model of determinant factors on the competence of graduates of life skills training based on partnerships with industry. The research method uses a quantitative approach designed with expost facto research. Data collection techniques with a scaled questionnaire. The research population was graduates of life skills training at the Semarang City Course and Training Institute (LKP) in the last 3 years. The sampling technique used simple random sampling 163 respondents. Data analysis using structural equation modeling with Confirmatory Factor Analysis to obtain overall model fit. The results of the research compiled a determinant model of the competence of graduates of life skills training is the alignment factor of the soft skills and hard skills learning outcomes curriculum integrated with industry competency needs, learning methods apply internship systems, product based training, on the job training with industrial partners, alignment of learning facilities and infrastructure based on information technology and process evaluation factors and the end of training learning with competency certification tests. Recommendations for Courses and Training Institutions in developing curricula to equip 21st century skills-oriented life skills graduate competencies, including soft skills competencies of critical thinking, creativity, digital literacy, collaboration and emotional intelligence and hard skills by conditioning learning in collaboration with industrial institutions.